Domino C–H Activation Reactions through Proximity Effects. Issue 40 (9th October 2018) - Lotz, Florian; Kahle, Klaus; Kangani, Mehrnoush; Senthilkumar, Soundararasu; Tietze, Lutz F.
Abstract : Proximity effects permit C–H activation reactions without directing groups. Here competitive reactions of selected substrates were investigated which allow a domino‐carbopalladation/Mizoroki–Heck reaction and a domino‐carbopalladation/C–H activation reaction. In the Pd‐catalyzed transformation of the enantio‐ and diastereopure alkyne8a the tetra‐substituted alkenes10 and11 were formed almost exclusively through a domino carbopalladation/Mizoroki–Heck reaction. In contrast, the diastereomer8c only led to the acenaphthylenes12c and13c through a domino carbopalladation/C–H activation reaction. Moreover, in the reaction of20, 24 and27 containing a naphthyl moiety only the tetra‐substituted alkenes23, 25 /26 and28 /29, respectively were obtained, whereas in the reaction of34, containing a phenanthrene moiety, compound37 was the only product, formed via a C–H activation reaction. Abstract : Proximity effects allow C–H‐activation reactions without directing groups in competition with domino‐carbopalladation or Mizoroki–Heck reactions. Vinly–Pd species can be assumed as intermediates, which either react with a double bond or a naphthyl or phenanthryl moiety.